Supine percutaneous nephrolithotomy with endoscopic combined intrarenal surgery — results of the first one hundred patients from a single UK centre. (November 2013) - Awsare, Ninaad S; Ghei, Maneesh; Rajkumar, Vellore; Jones, Paul A
Objective: To review our experience using combined supine PCNL and simultaneous ureterorenoscopy (ECIRS: endoscopic combined intrarenal surgery) to treat renal calculi. Patients and methods: Retrospective analysis of operative times, anaesthetic and surgical complications, and stone-free rates in patients who underwent PCNL and ECIRS in the Galdakao Modified Supine Valdivia position at a single centre between September 2007 and November 2011 was undertaken. Outcomes for those patients with BMI > 30 and those with high ASA grade were compared to the remaining patient group. Results: One hundred patients underwent 103 PCNL procedures. Thirty-one (31%) patients had BMI > 30 while 48 (48%) had ASA grade III or IV. Mean ± S.D. operative time and hospital stay was 111.34 ± 36.92 min and 49.5 ± 18.6 h respectively with no demonstrable increase in either parameter for patients with high ASA grade or BMI. The overall PCNL stone-free rate was 87% with 13 needing a secondary procedure. Six patients had postoperative complications (three transfusions, two post-operative fever and one ITU admission for sepsis). Conclusions: Supine PCNL incurs minimal anaesthetic morbidity. The GMSV position enables PCNL to be performed in the obese safely with high stone-clearance rates when combined with ECIRS thus decreasing the need for ancillary procedures such as ESWL.